Why We Can't Wait: A Guide for Black Student Achievement Programs - Gilman W. Whiting; Julia L. Nyberg (MDPI AG, 2024)
Black student achievement is vital. There must be a focused national effort to establish and sustain Black Student Achievement Programs (BSAPs). The development of BSAPs centers on African American history, culture, language, knowledge, and values. This article describes Black Student Achievement Program standards and the components of service design, curriculum and instruction, scholar identity development, and social and emotional needs, connecting the home and community for Black students in K-12th grade settings. Educators can play a vital role in the efforts to build and sustain BSAPs at their school sites and school districts.